Decontextualized Religious Metaphors in Yasmina Khadra's In Les Agnaux du Seigneur - Houria BENNACER & Lynda CHOUITEN (Akofena)
Abstract: This article examines the religious discourse of terrorism in Yasmina Khadra’s Les Agneaux du Seigneur (1998), which terrorists used to set off a cycle of violence that repulsed Algerians during the Black Decade (1991-2000), following the annulment of the legislative election results that brought the F.I.S. to power. It also enhances understanding of terrorist’s discourse used to influence young people and entice them to affiliate with them. The paper is confined to analyzing the use of two theological terms imbued with negative connotations within the Islamic tradition and exploiting them to generate a degrading narrative regarding the victims of the terrorist organization. It also shows the danger of manipulating religious speech by removing it from its native context and weaponizing it for terrorist agendas, particularly when combined with other forms of dehumanization directed at individuals who oppose terrorist’s ideology and objectives. Keywords: metaphor; dehumanization; Hubal; Sodom; violence